The mediating effect of English self-efficacy on the relationships between motivation to learn, intention to share knowledge, and job performance among military personnel: a conceptual framework / Siti Haizam Mohd Zin and Mohammad Nazry - Mohd Zin, Siti Haizam; Nazry, Mohammad (Universiti Teknologi MARA, 2021)
Extensive research on the relationship between employees' use of English in the workplace and their job performance has revealed that the use of English at work leads to increased job performance and positive interactions among staff. In relation to this, a good command of English among military staff, especially officers, is of great importance to the Armed Forces, as military personnel often serve abroad and need to be proficient in communicating their instructions and orders to a foreign team. Although the extant literature supports the direct role of self-efficacy in determining job performance apart from intention to share knowledge and motivation to learn, self-efficacy in English skills has rarely been examined as a mediator that explains the effect of knowledge sharing intention and learning motivation on job performance. Therefore, this paper aims to develop a conceptual framework that can be used to improve the understanding of English self-efficacy and its relationship with employees’ motivation to learn, intention to share knowledge, and capability to perform a job. This framework informs and guides future research that will test the hypothesized relationships. The findings would assist the Human Resource Department, Defense Operations and Training Departments and Education Directorate of the Malaysian Armed Forces to design or revise military training syllabi and approaches.